2021
DOI: 10.3390/su13095169
|View full text |Cite
|
Sign up to set email alerts
|

How Ready Is Higher Education for Quality 4.0 Transformation according to the LNS Research Framework?

Abstract: The world is evolving, and it has transformed from the industrial age to the era of connected and intelligent products in both organizations and competition. The advances in technology in the last decade have led to the introduction of a new term called Industry 4.0 or the fourth industrial revolution and that has led to the emergence of the term Quality 4.0. Quality 4.0 is the digitalization of traditional quality approaches and the focus on the use of digital tools to improve an organization’s ability to mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 83 publications
0
75
0
3
Order By: Relevance
“…Figure 4 can be large even if there is no direct relationship between the positions. It is evident that the main authors in this analysis were Alzahrani et al [ 1 ] and Ocheja et al [ 22 ] in terms of annual correlation.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Figure 4 can be large even if there is no direct relationship between the positions. It is evident that the main authors in this analysis were Alzahrani et al [ 1 ] and Ocheja et al [ 22 ] in terms of annual correlation.…”
Section: Resultsmentioning
confidence: 89%
“…In addition, Ali et al [ 26 ] introduced blockchain model to support easy application for certificates. Alzahrani et al [ 1 ] indicated the limited blockchain adoption in support of IES quality. Moreover, Panachev et al [ 9 ] investigated the use of blockchain and game approach in higher education institutions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant moment for the development of communication support systems for solutions based on incremental technologies was the emergence of cloud computing. These technologies have revolutionized many areas of our life [30][31][32], and thus also influenced the area related to 3D printing. Resource virtualization ensured scalability of design and manufacturing systems, and thus it was possible to increase the efficiency of use, reduce costs and extend cooperation in both B2B and B2C relations [9,[33][34][35].…”
Section: Development Of Network Communication In 3d Printing Systemsmentioning
confidence: 99%